Damage mechanics of electromigration in microelectronics copper interconnects. (1st June 2007) - Basaran, Cemal; Lin, Minghui
Current density levels are expected to increase by orders of magnitude in nanoelectronics. Electromigration which occur under high current density is the major concern for the nanoelectronics industry. Using a general purpose computational model, which is capable of simulating coupled electromigration and thermo-mechanical stress evolution, several dual damascene copper interconnect structures have been investigated for electromigration damage. Different diffusion boundary conditions including blocking and non-blocking boundary conditions, current crowding effects, interface diffusion effects and material plasticity have been considered. Different damage criteria are used for quantifying material degradation. The computational simulation results match the experimental findings; therefore the model proves to be a useful tool for quantifying damage in nanoelectronics interconnects.